2012
DOI: 10.1007/s12282-012-0364-z
|View full text |Cite
|
Sign up to set email alerts
|

Non-mass-like lesions on breast ultrasonography: a systematic review

Abstract: This article reviews various non-mass-like ultrasonography (US) findings of the breast and the sonographic-pathologic correlation with Doppler techniques, elastography, and MRI. High-resolution US allows for identification of small, clinically occult non-mass-like US findings. Ductal carcinoma in situ and invasive lobular carcinoma usually manifest as a non-mass-like lesion on US. It is useful to classify non-mass-like lesions on US in a similar manner to the classification of non-mass-like enhancement on MRI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
60
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(66 citation statements)
references
References 13 publications
6
60
0
Order By: Relevance
“…There have been a few studies regarding NMLs on breast US [3][4][5][6]13] and all of these studies had different inclusion criteria. Morishima et al [13] reported the sonographic characteristics of breast cancer that showed NMLs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been a few studies regarding NMLs on breast US [3][4][5][6]13] and all of these studies had different inclusion criteria. Morishima et al [13] reported the sonographic characteristics of breast cancer that showed NMLs.…”
Section: Discussionmentioning
confidence: 99%
“…DCIS lesions have been reported to be identified as NMLs of ductal or non-ductal pattern with or without echogenic spots corresponding to the mammographic findings [7,8] and Shin et al [9] reported that 17 of 106 DCIS lesions (16%) were shown as NML on screening detected DCIS. ILC also may not form a mass because it is composed of non-cohesive cells individually dispersed or arranged in a single-file linear pattern within fibrous stroma [4,10]. In Selinko et al series [12], 15% of ILC were described as an ill-defined area of altered, hypoechoic, inhomogeneous echotexture without identifiable margins and without frank shadowing.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only malignant lesions, but also non-malignant lesions can also appear as non-mass-like lesions, such as adenosis, intraductal papilloma and plasma cell mastitis. Some studies classified the "hypoechoic area" into ductal hypoechoic area and nonductal hypoechoic area according to whether they describe patterns reminiscent of the milk duct system or those reminiscent of glandular tissue [13]. However, this classification was derived from MRI and it is not suitable for US findings.…”
Section: Discussionmentioning
confidence: 99%